Enhancing English Achievement through Moodle LMS: Evidence from an Indonesian Boarding School - Afif Zuhdy Idham; Mulyarti Mulyarti; Wahyuddin Rauf; Arfah Hamzah; Abd. Rajab (Faculty of Education and Teacher Training of UIN Palopo, 2025)
The integration of technology into education is increasingly vital, yet evidence regarding its effectiveness in specific learning contexts remains limited. This study addresses that gap by examining the impact of Moodle as a Learning Management System (LMS) on students’ English learning outcomes in a boarding school setting. A quasi-experimental pretest–post-test design was employed with 70 students divided equally into experimental and control groups. The experimental group was taught through Moodle LMS, while the control group received instruction via conventional lectures. Data were collected through tests, observations, interviews, and documentation, and analysed using descriptive and inferential statistics. Results revealed improvement in both groups, but the experimental group achieved significantly higher post-test scores, as confirmed by t-test analyses (p < 0.01). These findings demonstrate that Moodle LMS not only enhances academic performance but also promotes greater engagement, active participation, and access to structured learning resources. The study underscores the pedagogical potential of Moodle, particularly within boarding school environments, where students benefit from continuous, technology-supported interaction. The research contributes to growing evidence on the role of LMS platforms in fostering 21st-century learning and recommends their broader implementation to strengthen English language instruction and digital literacy skills.